The borderless world : - Ohmae, Kenichi (HarperBusiness, 1990)
The Borderless World has changed the way managers view the world and their businesses, and how they invent, marker, and compete in our new globally interlinked economy. Kenichi Ohmae's groundbreaking bestseller argues persuasively how national borders are less relevant than ever before and identifies key characteristics of top--performing nations and corporations